6ab^2-(q-r)^2
7 answers
and what do you need help with?
Factoring....
6(ab)2
Do you mean the original question should have been to factor
6(ab)^2-(q-r)^2 ?
That is the difference of two squares.
Follow the appropriate procedure.
6(ab)^2-(q-r)^2 ?
That is the difference of two squares.
Follow the appropriate procedure.
what procedure?
For any quantities A and B
A^2 - B^2 = (A+B)(A-B)
In your case, let A = ab*sqrt6 and B = (q-r)
then write down the two factors in terms of a, b, q and r
A^2 - B^2 = (A+B)(A-B)
In your case, let A = ab*sqrt6 and B = (q-r)
then write down the two factors in terms of a, b, q and r
i need help On graphing